2007
DOI: 10.1097/01.brs.0000259922.82413.72
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of Drop Foot Caused by Degenerative Lumbar Diseases

Abstract: Palsy duration and preoperative strength were factors that most affected drop foot recovery following surgical intervention for spinal degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 12 publications
3
89
1
Order By: Relevance
“…More than half (55.6%; 5 of 9 patients) the patients with preoperative drop foot showed residual gait disturbance (Table 2). A previous study on the surgical outcome of LSS patients with drop foot revealed that especially those with a preoperative MMT score of 0 or 1 for ankle dorsiflexion exhibited poor alleviation of this disorder [1]. In the present study as well, there were three patients with an MMT score of 0 or 1, and all of them showed residual gait disturbance due to the unchanged drop foot (data not shown).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…More than half (55.6%; 5 of 9 patients) the patients with preoperative drop foot showed residual gait disturbance (Table 2). A previous study on the surgical outcome of LSS patients with drop foot revealed that especially those with a preoperative MMT score of 0 or 1 for ankle dorsiflexion exhibited poor alleviation of this disorder [1]. In the present study as well, there were three patients with an MMT score of 0 or 1, and all of them showed residual gait disturbance due to the unchanged drop foot (data not shown).…”
Section: Discussionmentioning
confidence: 51%
“…In fact, a prospective study revealed that the surgery generally resulted in a more preferable greater outcome than non-surgical treatments in the LSS patients [20]. However, about 20-40% of patients have been reported to be dissatisfied with the result due to residual symptoms [1,8,9]. To avoid the discrepancy between a patient's expectations and actual surgical outcome, a surgeon should preoperatively inform the patient in detail of the possible post-surgery outcome of the major symptoms such as leg pain/numbness and gait disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Drop foot was defined as a tibialis anterior muscle strength score less than 3 (of 5) [1,2,6,8]. Tibialis anterior muscle strength was graded as 3-when patients could dorsiflex and invert their ankles while they were seated but could not achieve full ROM.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…Tibialis anterior muscle strength was evaluated using a manual muscle test according to the Medical Research Council scale and as described in a previous study (Table 1) [1]. Drop foot was defined as a tibialis anterior muscle strength score less than 3 (of 5) [1,2,6,8].…”
Section: Clinical Assessmentmentioning
confidence: 99%
See 1 more Smart Citation